Evaluation of the modified HTK solution in pancreas transplantation: an experimental model - Esmaeilzadeh, Majid; Fonouni, Hamidreza; Golriz, Mohammad; Majlesara, Ali; Kuttymuratov, Gani; Bergmann, Frank; Jarahian, Parvin; Khazaeipour, Zahra; Faridar, Alireza; Rad, Morva Tahmasbi; Longerich, Thomas; Gebhard, Martha-Maria; et al. (Asian journal of surgery, 2016)
Introduction - One of the great challenges in pancreas transplantation is the ischemia reperfusion injury. It is mentioned that free oxygen and/or nitrogen radicals play a prominent role in this phase. To minimize this problem, a modified histidine-tryptophan-ketoglutarate (HTK) solution that contains modified antioxidants has been developed. Our aim was to evaluate this solution in improving the viability of the pancreas in comparison with standard HTK and University of Wisconsin (UW) solutions in a porcine model of pancreas transplantation. - Materials and methods - Twenty-three Landrace pigs were divided into three identical groups. After a 10-hour preservation time at 4°C, the pancreas was implanted in the organs of the recipients in a standardized manner. Serum parameters were assessed prior to and after implantation on the 1st postoperative day, 3rd postoperative day, and 7th postoperative day. Furthermore, three biopsies were taken: prior to and after reperfusion, and on Day 7 to assess the grafts. - Results - An analysis of serum glucose among the three groups showed no significant differences. Evaluation of the insulin levels showed no significant difference between the modified and standard HTK groups; however, differences between HTK and UW were significant (p = 0.004 in favor of UW solutions). The histopathological results showed a trend of a higher grade of rejection of pancreas tissue in the UW group compared to both HTK groups. - Conclusion - The modified HTK solution could preserve the pancreas for the preservation of the graft with similar results to those observed for standard solutions without any significant difference. The trend showed that the pathological finding in the UW group was not as good as that in the modified HTK and standard HTK groups.
Gesehen am 11.05.2020
Available online 26 July 2015